TEETH PREPERATION FOR ELECTRON SPINNING RESONANCE (ESR) DATING METHOD - Anton Ferdianto (Pubawidya: Jurnal Penelitian dan Pengembangan Arkeologi, 2018)
Fossil bones and teeth usually are very common archeological findings. At many sites these remains, such as bones bearing cut marks, may provide unequivocal evidence for human occupation. Hence bones and teeth provide the ideal targets for directly dating of archeological levels. Combined ESR/U-series dating of fossil teeth has been increasingly used in geochronological research over the past three decades. Results prove that it can be potentially applied to the sites in different geological contexts (fluvial/lacustrine or karstic environments) over a timescale of 304-206 years. But to perform this dating method, there’s a step that we need to prepare and do. This article try to explain the procedure how we prepare teeth step by step until it’s ready to be measure.